Information system to enhance medical services quality in Indonesia - Susana Limanto; Andre Andre (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The consequence of disproportionate distribution and placement of Doctor in Indonesia is affecting people who live in rural area. Patient have to travel to city to receive medical treatment and must encounter another different problem such as: patients often have to wait a long time in the doctor's office even sometimes do not get the service because of holiday or rejected because the queue is full. Medical record in some cases may lost due in Indonesia mostly medical record recorded manually (paper based). Therefore doctor treatment is not optimal because doctor can no longer inspect patient illness history and any treatment that have been conducted before. This research proposes a new concept to help people who live in rural area to get better medical treatment. People could register and monitor doctor service queue via smart phone. System expanded with medical record management facilities to improve service quality of patient. Research object was doctor service in Sulawesi, Indonesia. This research indicates system could increase time efficiency, energy, and cost efficiency for patient and also the doctor. Additionally current system will be optimal if supported with stable internet network.